Screening #MeToo : rape culture in Hollywood - Funnell, Lisa, 1980-; Beliveau, Ralph (SUNY Press, 2022)
Considers how Hollywood films since the 1960s have both reflected and shaped attitudes toward rape and sexual violence.
Keywords: Motion picture industry -- Social aspects -- California -- Los Angeles -- History.; Sex crimes -- California -- Los Angeles -- History.; MeToo movement.; Cinéma -- Industrie -- Aspect social -- Californie -- Los Angeles -- Histoire.; Violence sexuelle -- Californie -- Los Angeles -- Histoire.; Mouvement #MoiAussi.; PERFORMING ARTS / Film / History & Criticism; MeToo movement; Motion picture industry -- Social aspects; Sex crimes; California -- Los Angeles; History